(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The study aimed to identify the impact of human resources management strategies on business continuity in the developed global markets company, in addition to identifying the impact of the performance level of human resources management strategies in the developed global markets, as well as knowing the level of business continuity application in the developed global markets company, and revealing the impact and the extent of the link And the relationship between the dimensions of human resource management strategies and business continuity, and to achieve the purpose of the study, the descriptive analytical approach was adopted, where the data was collected through electronically distributing the questionnaire. The study population consisted of (215) male and female employees, where 200 valid questionnaires were retrieved for analysis, and then the analysis was done using the SPSS statistical package. The study reached a set of results, the most prominent of which was that the strategies of human resource management (recruitment, training, evaluation) have a statistically significant impact on business continuity in its dimensions (management support, evaluation, plans). Based on the results, a number of recommendations were reached, the most prominent of which are: the need to strive to increase investment in human resources and development and to link between human resources management strategies, the need for continuous attention to developing plans for development and training for all employees in the developed global markets company to ensure their permanent readiness for any new coordinates at work.